Variational fluid flow measurements from image sequences: synopsis and perspectives - Heitz, Dominique; Mémin, Etienne; Schnörr, Christoph (Experiments in fluids, 2010)
Variational approaches to image motion segmentation has been an active field of study in image processing and computer vision for two decades. We present a short overview over basic estimation schemes and report in more detail recent modifications and applications to fluid flow estimation. Key properties of these approaches are illustrated by numerical examples. We outline promising research directions and point out the potential of variational techniques in combination with correlation-based PIV methods, for improving the consistency of fluid flow estimation and simulation.